2021
DOI: 10.3390/cancers13020358
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Advanced Gastro-Entero-Pancreatic Neuro-Endocrine Tumors: A Systematic Review and Network Meta-Analysis of Phase III Randomized Controlled Trials

Abstract: Several new therapies have been approved to treat advanced gastro-entero-pancreatic neuroendocrine neoplasms (GEP–NENs) in the last twenty years. In this systematic review and meta-analysis, we searched MEDLINE, ISI Web of Science, and Scopus phase III randomized controlled trials (RCTs) comparing two or more therapies for unresectable GEP–NENs. Network metanalysis was used to overcome the multiarm problem. For each arm, we described the surface under the cumulative ranking (SUCRA) curves. The primary endpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…This problem was overcome using the NMA methodology already validated in surgical [50] and oncology literature [51]. About the primary endpoint, we observed that the differences among the different interventional approaches were minimal, and none of them was near to an ideal treatment.…”
Section: Discussionmentioning
confidence: 94%
“…This problem was overcome using the NMA methodology already validated in surgical [50] and oncology literature [51]. About the primary endpoint, we observed that the differences among the different interventional approaches were minimal, and none of them was near to an ideal treatment.…”
Section: Discussionmentioning
confidence: 94%
“…SSAs are the mainstay of treatment of well-differentiated GEP-NET since they showed antiproliferative effect [ 7 , 8 ] with a very tolerable safety profile [ 31 , 32 ]. Subsequent treatment lines at progression include PRRT, TKIs, or chemotherapy, all of which have a toxicity profile less favorable than SSAs, with PRRT preferred over other alternatives [ 33 , 34 ]. Non-conventional doses SSA (HD-SSA), achieved by either dose density or dose intensity increase, have been proposed and investigated as a potential treatment option in patients with GEP-NET whose disease progressed on standard dose SSA.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, available literature and the results of our meta-analysis suggest that HD-SSA is not the preferred treatment choice in patients with GEP-NET who progressed on standard-dose SSA because of the short PFS and low DCR reported, especially when compared with other alternatives, such as PRRT [ 12 , 33 ]. This is markedly more evident in studies carried out in the USA, with prospective design, and in patients with metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective multicenter Italian study showed that [ 177 Lu]Lu-DOTA-TATE, as well as non-conventional-dose somatostatin analogues [ 186 ], are better tolerated than chemotherapy or everolimus, with no significant difference in PFS [ 187 ]. Because a recent network meta-analysis showed that [ 177 Lu]Lu-DOTA-TATE had the highest probability of being associated with the longest PFS as compared to other approved treatments [ 188 ], it is not surprising that ongoing studies—namely, the NETTER-2 (NCT03972488) and COMPETE trials (NCT03049189)—aim at first-line positioning of PRRT. Nevertheless, shifting PRRT to earlier in the treatment algorithm for patients with NETs is associated with poorer tolerance of subsequent treatments, such as everolimus [ 189 ], or might not be associated with improved outcomes, e.g., in patients with pancreatic NETs [ 190 ].…”
Section: Somatostatin Analogues For Targeted Therapymentioning
confidence: 99%